Tackling vitamin A deficiency with biofortified sweetpotato in sub-Saharan Africa - Low, Jan W.; Mwanga, Robert O.M.; Andrade, M.I.; Carey, E.E.; Ball, Anna-Marie (Elsevier, 2017)
Orange-fleshed sweetpotato (OFSP) is a rich plant-based source of beta-carotene, which the body converts into vitamin A. In sub-Saharan Africa, sweetpotato is known as a food security crop but most varieties grown are high dry matter white-fleshed types, lacking beta-carotene. In 1995, researchers recognized the potential of OFSP varieties to address widespread vitamin A deficiency in SSA using an integrated agriculture-nutrition approach. With their partners, they confronted conventional wisdom concerning food-based approaches and institutional barriers, to build the evidence base and breed 42 OFSP varieties adapted to farmer needs and consumer preferences. Subsequently, a multi-partner, multi-donor initiative, launched in 2009, has already reached 2.8 million households. This review summarizes that effort describing how the changing policy environment influenced the process.